The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/14651858.cd012161
|View full text |Cite
|
Sign up to set email alerts
|

Short-acting insulin analogues versus regular human insulin for adults with type 1 diabetes mellitus

Abstract: Our analysis suggests only a minor benefit of short-acting insulin analogues on blood glucose control in people with type 1 diabetes. To make conclusions about the effect of short acting insulin analogues on long-term patient-relevant outcomes, long-term efficacy and safety data are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
2
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 106 publications
8
40
2
7
Order By: Relevance
“…Even in the face of a lack of scientific evidence concerning the superiority of the insulin analogues over human insulin 9,10 , the doctors prescribed them including for patients who were not in a good financial position to purchase them outright. In the prescriptions or doctors' reports that would reinforce the lawsuits, they alleged the necessity of the patient in using the insulin analogues even though there was no proof to justify their choice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even in the face of a lack of scientific evidence concerning the superiority of the insulin analogues over human insulin 9,10 , the doctors prescribed them including for patients who were not in a good financial position to purchase them outright. In the prescriptions or doctors' reports that would reinforce the lawsuits, they alleged the necessity of the patient in using the insulin analogues even though there was no proof to justify their choice.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the position of the doctors goes against what the clinical studies 9,10 have shown which indicates that insulin analogues do not present any relevant advantages over human insulin. Secondly, the SUS managers have differing positions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Education regarding matching prandial insulin doses to carbohydrate intake, pre-meal glucose levels, and anticipated activity should be considered when planning insulin regimens for those with type 1 diabetes mellitus. The glycaemic control achieved is comparable between regular (soluble) insulin and the newer rapid acting analogues [3,26] and between NPH insulin and the newer long acting analogues [11,12].…”
Section: Place Of Newer Antidiabetics In Therapymentioning
confidence: 96%
“…The recommendation that most individuals with type 1 diabetes mellitus should use rapid-acting insulin analogs to reduce hypoglycemia risk [22], should be weighed against the cost and the lack of a significant difference in terms of glycaemic control [3,26] when compared with regular (soluble) insulin, which is cheaper.…”
Section: Place Of Newer Antidiabetics In Therapymentioning
confidence: 99%